Formulasi Sediaan Suspensi Ekstraksi Labu Air (Lagenaria siceraria (Molina) Standly) dan Madu Multiflora dengan Natrium Alginat Sebagai Bahan Pensuspensi - Aisyah Muthmainnah; Solikah Ana Estikomah; Sri Wahyuni (University Of Darussalam Gontor, 2022)
Water gourd is a fruit that has a high water content efficacious as a medicine for high fever due to typhoid or infection because it has a cooling effect. This study aims to make a suspension of water gourd extract and multiflora honey as a therapy for typhoid. Suspension preparations are expected to provide a faster therapeutic effect and have good stability. Three suspension formulations were made with sodium alginate as a suspending agent with a concentration of 1%, 3%, 5% suspending agent. Evaluation of suspension preparations included sedimentation volume, redispersion, organoleptic, particle size, pH level, and viscosity. The best and most stable suspension formulations were suspension preparations with a concentration of 1%.